2022
DOI: 10.1007/s11033-022-07419-9
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and REGN-CoV2 combination as a vaccine adjuvant for Omicron variant of SARS-CoV-2

Abstract: The omicron variant (B.529) of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which emerged in late 2021, caused panic worldwide due to its contagiousness and multiple mutations in the spike protein compared to the Delta variant (B.617.2). There is currently no specific antiviral available to treat Coronavirus disease 2019 (COVID-19). However, studies on neutralizing monoclonal antibodies (mAb) developed to fight COVID-19 are growing and gaining traction. REGN-COV2 (Regeneron or imdevimab-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…A cross-sectional clinical trial experiment and adjuvant therapy found that the dose of 3 to 10 mg of melatonin has preventative and therapeutic effects for COVID-19 disease, but it must be further evaluated, especially in children, and the efficacy of melatonin against the Omicron variant requires investigation [ 45 , 48 ]. Recently, a mini review hypothesized, according to an experiment, that melatonin with REGN-CoV-2 adjuvant therapy might significantly prevent the infection of Omicron variant in immunocompromised and elderly patients [ 49 ].…”
Section: Anti-oxidative Effects Of Melatoninmentioning
confidence: 99%
“…A cross-sectional clinical trial experiment and adjuvant therapy found that the dose of 3 to 10 mg of melatonin has preventative and therapeutic effects for COVID-19 disease, but it must be further evaluated, especially in children, and the efficacy of melatonin against the Omicron variant requires investigation [ 45 , 48 ]. Recently, a mini review hypothesized, according to an experiment, that melatonin with REGN-CoV-2 adjuvant therapy might significantly prevent the infection of Omicron variant in immunocompromised and elderly patients [ 49 ].…”
Section: Anti-oxidative Effects Of Melatoninmentioning
confidence: 99%
“…As a result, detrimental consequences such as DNA damage, protein oxidation, and lipid peroxidation can be avoided [50]. Matrix metalloproteinase (MMP) expression is increased due to reactive oxygen species [1]. The negative consequences of excessive MMP production can be significantly diminished by melatonin supplementation with ROS scavenging action [1,40].…”
Section: Effects Of Melatonin As An Antioxidant and Anti-inflammatory...mentioning
confidence: 99%
“…Matrix metalloproteinase (MMP) expression is increased due to reactive oxygen species [1]. The negative consequences of excessive MMP production can be significantly diminished by melatonin supplementation with ROS scavenging action [1,40]. Melatonin could help to alleviate the pulmonary inflammation brought on by COVID-19 by reducing oxidative stress and cell death.…”
Section: Effects Of Melatonin As An Antioxidant and Anti-inflammatory...mentioning
confidence: 99%
See 2 more Smart Citations